Factors Affecting APBN Performance With Organizational Commitment as a Moderating Variable at The Ministry of Finance - Sari, Okta Purnama; Periansya, Periansya; Sari, Yuliana (Universitas Merdeka Pasuruan, 2025)
This study examines the effect of good governance and non-tax state revenue on APBN performance with organizational commitment as a moderating variable at the Ministry of Finance in the DJKN Regional Offices of South Sumatra, Jambi, and Babel. The research sample consisted of 55 employees with a saturated sampling technique. Data collection was conducted using an interval scale questionnaire. Data analysis involved descriptive statistics, classical assumption tests, multiple linear regression analysis, Moderated Regression Analysis (MRA), and hypothesis testing using IBM SPSS 27 for Windows. The results of the study indicate that good governance and non-tax state revenue partially have a significant and positive effect on APBN performance. Organizational commitment is proven to moderate and strengthen the relationship between good governance and non-tax state revenue with APBN performance. Simultaneously, the variables of good governance and non-tax state revenue also have a significant and positive effect which is further strengthened by the presence of organizational commitment.